Fungi in Horticultural Crops: Promotion, Pathogenicity and Monitoring - Quanzhi Wang; Yibing Han; Zhaoyi Yu; Siyuan Tian; Pengpeng Sun; Yixiao Shi; Chao Peng; Tingting Gu; Zhen Li (Agronomy, 2025)
In this review, we aim to provide a comprehensive overview of the roles of fungi in horticultural crops. Their beneficial roles and pathogenic effects are investigated. In addition, the recent advancements in fungal detection and management strategies (especially the use of spectral analysis) are summarized. Beneficial fungi, including plant growth-promoting fungi (PGPF), ectomycorrhizal fungi (ECM), and arbuscular mycorrhizal fungi (AMF), enhance nutrient uptake, promote root and shoot development, improve photosynthetic efficiency, and support plant resilience against biotic and abiotic stresses. Additionally, beneficial fungi contribute to flowering, seed germination, and disease management through biofertilizers, microbial pesticides, and mycoinsecticides. Conversely, pathogenic fungi cause significant diseases affecting roots, stems, leaves, flowers, and fruits, leading to crop yield losses. Advanced spectral analysis techniques, such as Fourier Transform Infrared Spectroscopy (FTIR), Near-Infrared Spectroscopy (NIR), Raman, and Visible and Near-Infrared Spectroscopy (Vis-NIR), alongside traditional methods like Polymerase Chain Reaction (PCR) and Enzyme-Linked Immunosorbent Assay (ELISA), have shown promise in detecting and managing fungal pathogens. Emerging applications of fungi in sustainable agriculture, including biofertilizers and eco-friendly pest management, are discussed, underscoring their potential to enhance crop productivity and mitigate environmental impacts. This review provides a comprehensive understanding of the complex roles of fungi in horticulture and explores innovative detection and management strategies.